Anxiety among Cameroonian dentists during the COVID-19 pandemic: A cross-sectional web-based survey - Messina Ebogo; Celestin Danwang; Francky Teddy Endomba (Elsevier, 2021)
Objective: To assess anxiety among dentists practicing in Cameroon during the coronavirus disease 2019 (COVID-19) pandemic. We conducted a cross-sectional web-based survey, and used the Hamilton Anxiety Rating Scale (HAM‐A) to appraise anxiety symptoms and severity. Results: Overall, 82 questionnaires were fully completed and retained for analysis. The mean age (standard deviation) of participants was 30.2 (2.6) with 52 (62.2%) being male. The mean (standard deviation) HAM-A score was 10.5 (4.6), with minimum and maximum values of 4 and 26/56. We found that 13 (15.8%) had moderate to severe anxiety (with 11 having moderate symptoms and 2 having severe), and 69 (84.2%) had no, minimal or mild anxiety. Participants working in health facilities with more than one dentist, where less likely to have moderate/severe anxiety (OR: 0.22, 95% CI: 0.05; 0.78).